Pengaruh kepimpinan bervisi pengetua terhadap budaya sekolah dan komitmen organisasi di sekolah menengah atas (SMA) di Sumatera Selatan Indonesia - Parmin (2018)
A principal with a vision is a driven principal that focuses on achieving the clear visions by encouraging all party to achieve the school’s goals effectively through various productive programmes and activities. The competency of school principals in South Sumatera is extremely low due to the lack of leadership skills. This factor will have an impact on the low cultural quality of the school as well as the commitment of teachers in the Senior High School in South Sumatra. This research aims to explore the influence of the principal’s visionary leadership towards the school cultures and organizational commitment in South Sumatera Indonesia. This quantitative study involved 314 public high school and 329 private high school teachers were identified through the stratified proportionate sampling. The research survey design is through cross-sectional. The instruments used are Visionary Leadership, School Culture and Organizational Commitment. Descriptive statistics, Pearson Correlation, t-test and multiple regressions were employed to analyze the data based on the objectives of the study. The finding shows that the variables of open system, rational goal and internal processes are proven significant as moderating role between the principal’s visionary leadership and organizational commitment. The findings are expected to be used by the Education Department to identify the characteristics of the school principals, the influence of organizational culture and the commitment of the organization as a benchmark for better planning of the national education in the future.